Prävention sexuellen Kindesmissbrauchs im Dunkelfeld – das Hamburger Modell - Briken, Peer; Berner, Wolfgang; Flöter, Annika; Jückstock, Vivian; von Franqué, Fritjof (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2018)
Sollte Menschen, die ein sexuelles Interesse an Kindern haben, die Missbrauchsabbildungen nutzen oder befürchten, sexuelle Missbrauchshandlungen an Kindern zu begehen, ein Therapieangebot im Dunkelfeld gemacht werden? Sollte dies ein zentraler Bestandteil der Prävention sexuellen Kindesmissbrauchs sein? Wie sollte ein solches Angebot aussehen, damit es das Ziel, die Prävention von Kindesmissbrauch, erfüllen kann?A large proportion of child sexual offenses are not reported or convicted. At the same time, not all individuals who fulfil the diagnostic criteria for a pedophilic disorder do commit a child sexual offense. The purpose of the article is to present the Hamburg model for the treatment of pedophilic men or those with a risk of child sexual offences outside the criminal law context. Special emphasis is placed on a sound diagnostic and a risk assessment procedure. The selection of a suitable therapy framework, the setting and the method is carried out according to the risk, need, responsivity model. Psychodynamically sound as well as cognitive behavioral therapy methods and the procedure for concomitant drug treatment are described. Finally, the special features in dealing with medical confidentiality and risk situations are discussed. Important for the Hamburg model, as for comparable other approaches in the future, is the study of the therapeutic effects.
Keywords: Pädophilie; Kindesmissbrauch; Psychotherapie; Prävention